Peripheral haematological manifestations in HIV infection and its relation to CD4 count - Jain, Lalit; Singh, Amit A.; Chauhan, Pratap S. (International Journal of Advances in Medicine, 2019)
Background: HIV infection is associated with a wide range of haematological abnormalities, which are amongst its most common complications. This study aims at discerning the peripheral haematological abnormalities associated with HIV infection and to correlate them with CD4 cell count. Methods: An observational cross-sectional study was conducted from March 2017 till August 2018. 109 patients in 15 years or more age group who were HIV positive by the NACO guidelines were included. Complete hemogram, serum iron studies, serum folate and vitamin B12 levels, and flowcytometric CD4 cell count analysis were done for all the patients. Various haematological parameters were compared between the patients with CD4 cell counts <200/µl (n=52) to those with counts >200/µl (n=57). By using student t-test, the p-value was calculated for various parameters. Results: Anaemia (58.7%), leucopenia (27.5%) and thrombocytopenia (17.4%) were seen with anaemia being the most common abnormality. Normocytic normochromic anaemia (65.6%) was the predominant type of anaemia. Overall analysis showed a statistically significant difference between two groups in haemoglobin concentration, RBC indices, serum ferritin values and absolute lymphocyte count; with p-value <0.05. Conclusions: The diagnosis and treatment of haematological disorders are essential in medical care of the HIV-infected patients. Thus, in resource limited setups, where CD4 count analysis is not possible, haematological abnormalities can be used as tools for monitoring HIV positive individuals and can aid in the treatment of the patients.